PENGARUH POLA PIKIR KEWIRAUSAHAAN ADVERSITY QUOTIENT DAN PENDIDIKAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA DI KOTA TANGERANG - Purwaningsih, Nining; Megaster, Teknik (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2019)
This study aims to determine the effect of Entrepreneurial Mindset, Adversity Question and Entrepreneurship Education on student entrepreneurial interest in the city of Tangerang. Entrepreneurship education is intended as a learning process to change students' attitudes and mindsets on entrepreneurial career choices. The sampling technique used is purposive sampling, Research respondents used were students from universities in the city of Tangerang. This research is included in quantitative research. The data source in this sztudy is primary data. The data is used by distributing questionnaires directly. The data analysis method used is Structural Equation Modeling (SEM) analysis with the help of LISREL software. Research Results show that entrepreneurial mindset influences entrepreneurial interest with a correlation value of 0.63, which means that entrepreneurial mindset has a positive direction towards entrepreneurial interest. , adversity quotient influences entrepreneurial interest with a correlation value of 0.58, which means adversity quotient has a positive directional effect on entrepreneurial interest. entrepreneurship education has an effect on entrepreneurial interest with a correlation value of 0.66 which means that entrepreneurship education has a positive influence on entrepreneurial interest.